Etiological characteristics and antibiotic sensitivity of causative agents of purulent-inflammatory diseases of the maxillofacial region - V.A. Shevchuk; N.V. Odushkina; M.V. Tkachenko; N.I. Kovalenko; V.O. Smorodskyi; I.H. Tkachenko; A.H. Soloviova (Zdorovʹe Rebenka)
Background. The rapid spread of antibiotic-resistant pathogens of infectious diseases is a global problem. The purpose of this study was to determine antibiotic sensitivity of causative agents of purulent-inflammatory diseases of the maxillofacial region. Materials and methods. The medical records of 59 patients aged from 2 months to 17 years were examined retrospectively. The results of microbiological examination of wound discharge and sensitivity of bacteria to antibiotics were analyzed. Results. Sixty-two isolated bacterial strains were identified, mainly S.aureus (46.8 %), S.еpidermidis (12.9 %) and S.pneumoniae (12.9 %). Other bacteria (E.faecalis, S.viridans, P.diminuta, Lactobacillus spp., Prevotella spp. and Peptostreptococcus spp.) were detected in less than 10 % of cases. All strains of S.aureus, S.epidermidis, S.pneumoniae exhibited sensitivity to penicillinase-resistant penicillins, oxacillin, cefepime, ceftaroline, ceftobiprole, carbapenems, rifampicin, oxazolidinones. Staphylococci were also sensitive to cefazolin, cefadroxil, cephalexin, cefaclor, aminoglycosides, tigecycline, moxifloxacin. Staphylococcus had the superresistance to benzylpenicillin, ampicillin, ticarcillin, piperacillin (68–80 %), pneumococcus — to norfloxacin (80 %). S.aureus was resistant to macrolides, tetracyclines, chloramphenicol. S.epidermidis was resistant to macrolides, cefuroxime, ceftriaxone, and cefotaxime. Pneumococcus exhibited resistance to macrolides, tetracyclines and ampicillin. The amount of resistant strains of S.epidermidis, S.aureus and S.pneumoniae was 87.5, 75.7, and 62.5 %, respectively. The number of antibiotics to which S.aureus was resistant ranged from 6 to 13, S.epidermidis — from 1 to 7, and S.pneumoniae — from 1 to 8. Conclusions. Among the pathogens of purulent-inflammatory diseases of the maxillofacial region, gram-positive facultative anaerobic bacteria predominate, primarily S.aureus, S.epidermidis, and S.pneumoniae, which have multiple resistance to antibiotics.